Bidirectional Longitudinal Study of Frailty and Depressive Symptoms Among Older Chinese Adults - Cao, Limin; Zhou, Yuhan; Liu, Huiyuan; Shi, Mengyuan; Wei, Yingliang; Xia, Yang (Frontiers in Aging Neuroscience, 2022)
Objective: Frailty and depression, as two common conditions among older adults in China, have been shown to be closely related to each other. The aim of this study was to investigate the bidirectional effects between frailty and depressive symptoms in Chinese population. Methods: The bidirectional effect of frailty with depressive symptoms was analyzed among 5,303 adults ≥60 years of age from the China Health and Retirement Longitudinal Study (CHARLS). Phenotype and a frailty index were used to measure frailty. Depressive symptoms was evaluated using the Epidemiological Studies Depression Scale (CES-D). Logistic regression and Cox proportional hazard regression models were used to determine the bidirectional effects of frailty and depressive symptoms in cross-sectional and cohort studies, respectively. Subgroup and sensitivity analyses were further used to further verify the associations. Results: In the cross-sectional study, the multivariate-adjusted ORs (95% CIs) for depressive symptoms among pre-frail and frail adults, as defined by the frailty index and phenotype, were 3.05 (2.68-3.49), and 9.78 (8.02-12.03), respectively. Depressed participants showed higher risks of pre-frailty and frailty [frailty index, 3.07 (2.69-3.50); and phenotypic frailty, 9.95 (8.15-12.24)]. During follow-up, the multivariate-adjusted HRs (95% CIs) for depressive symptoms among pre-frail and frail participants, as defined by the frailty index and phenotype, were 1.38 (1.22-1.57), and 1.30 (1.14-1.48), respectively. No significant relationship existed between baseline depressive symptoms and the incidence of frailty. Moreover, the results from subgroup and sensitivity analyses were consistent with the main results. Conclusion: Although a cross-sectional bidirectional association between depressive symptom and frailty has been observed in older (≥60 years old) Chinese adults, frailty may be an independent predictor for subsequent depression. Moreover, no effect of depressive symptoms on subsequent frailty was detected. Additional bidirectional studies are warranted in China.